Formulation of phosphorous rich organic manure from rock phosphate and its dose optimization for the improvement of maize (Zea mays L.). (14th August 2020) - Noor, Kinza; Sarwar, Ghulam; Shah, Sabir Hussain; Muhammad, Sher; Zafar, Ayesha; Manzoor, Muhammad Zeeshan; Murtaza, Ghulam
Abstract: Rock phosphate is a non-renewable resource and a basic raw material of all the water soluble phosphatic fertilizers. The experiment was conducted to estimate usage of different organic amendments on release of P from rock phosphate using maize ( Zea mays L.) as a test crop. In the first phase, phosphate rich organic manure (PROM) was prepared using cow dung, press mud and rock phosphate. In the second phase of study, efficiency of thus prepared PROM was evaluated for P release and uptake by maize plants. Treatments of the experiments were; T1 = Recommended NPK, T2 = Recommended NK + zero, T3 = Recommended NK + half Recommended P + Half P from PROM, T4 = Recommended NK = Recommended P + All recommended P from PROM, and T5 = Recommended NK + Recommended P + All recommended P from PROM. The results reveal that the combination of PROM and DAP improved the growth components of maize. PROM also indicated the changes to other soil associated properties like EC (dS m −1 ) and soil pH. Similarly, PROM and recommended N, K, P from DAP produced the highest value of organic matter (0.94%), soil phosphorus concentration (20.06 mg kg −1 ), soil potassium concentration (286.2 mg kg −1 ), nitrogen concentration in plants (3.12%), phosphorous concentration in plants (0.31%), and potassium concentration in plants (3.50%) as compared to other treatments. The results suggest that rock phosphate is an environmental friendly and can be used as an alternate tool to reduce the use of chemical fertilizers.